Penerangan Eksistensi Debus sebagai Bentuk Autentisitas Budaya Banten: Suatu Pendekatan Hermeneutika - Muhamad Tamamul Iman; Kessya Amanda Fitria (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to analyze the practice of debus in the Banten tradition using a hermeneutic approach. Existence illumination of debus in Karl Jaspers existential philosophical means to find relation between debus existence, debus players existence and their relation with Transcendental. Debus is a traditional martial art that has been passed down through generations in the Banten community. This tradition involves various mystical, ritualistic, and spiritual elements, making it intriguing to investigate through a hermeneutic perspective. The hermeneutic approach is employed to uncover the hidden meanings behind the debus practice. The study combines analyses of ancient texts, historical records, interviews with debus practitioners, and direct observations of debus performances to understand the cultural context, philosophy, and symbolism associated with the practice. The findings of this research are expected to provide a deeper understanding of the debus practice as part of Banten's cultural heritage and how this tradition remains relevant in modern society. Additionally, this research is also anticipated to offer fresh insights into the significance and meaning of the spiritual and mystical aspects inherent in the debus practice. With the hermeneutic approach, this research aims to unravel interpretative layers and comprehend how the debus practice in the Banten tradition serves as a valuable means of cultural expression and local identity. The outcomes of this research can contribute to strengthening cultural sustainability and preserving the debus practice for future generations.